2011
DOI: 10.1016/j.abb.2010.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for the inability of an oxygen atom donor ligand to replace the natural sulfur donor heme axial ligand in cytochrome P450 catalysis. Spectroscopic characterization of the Cys436Ser CYP2B4 mutant

Abstract: All cytochrome P450s (CYPs) contain a cysteinate heme iron proximal ligand that plays a crucial role in their mechanism of action. Conversion of the proximal Cys436 to Ser in NH 2 -truncated microsomal CYP2B4 (ΔCYP2B4) transforms the enzyme into a two-electron NADPH oxidase producing H 2 O 2 without monooxygenase activity [K.P. Vatsis, H.M. Peng, M.J. Coon, J. Inorg. Biochem. 91 (2002) 542-553]. To examine the effects of this ligation change on the heme iron spin-state and coordination structure of ΔC436S CYP2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…This feature is similar to the ligandto-metal charge transfer bands observed in ferric Mb at pH 6.8 and cyclohexylamine-ligated H93G Mb, suggesting that one of the high spin species present in MmpL3-E1 and MmpL11-E1 is a His-or Lys-ligated heme (44,45). The wavelength and sign of the broad positive feature centered at 594 nm is most similar to the positive ligand-to-metal charge transfer bands in three anionic oxygen-bound heme proteins as follows: alkaline H93G Mb (62); H93Y Mb (62); and C436S CYP2B4 (63). This suggests the presence of a second high spin (Tyr or Ser)-ligated heme.…”
Section: Discussionmentioning
confidence: 81%
“…This feature is similar to the ligandto-metal charge transfer bands observed in ferric Mb at pH 6.8 and cyclohexylamine-ligated H93G Mb, suggesting that one of the high spin species present in MmpL3-E1 and MmpL11-E1 is a His-or Lys-ligated heme (44,45). The wavelength and sign of the broad positive feature centered at 594 nm is most similar to the positive ligand-to-metal charge transfer bands in three anionic oxygen-bound heme proteins as follows: alkaline H93G Mb (62); H93Y Mb (62); and C436S CYP2B4 (63). This suggests the presence of a second high spin (Tyr or Ser)-ligated heme.…”
Section: Discussionmentioning
confidence: 81%
“…It is well known that a cysteine-to-serine mutation30 in P450-BM3 at the axial Fe-binding position C400S eliminates monooxygenation activity but enhances the efficiency of Fe III -to-Fe II reduction by using NADPH as a reductant26. Therefore, we tested P450-BM3 variant C400S in the Kemp elimination of 1 .…”
Section: Resultsmentioning
confidence: 99%
“…We have recently demonstrated that the axial ligand mutant H93Y Mb, phenol-bound cavity mutant H93G Mb (which lacks the proximal His), and an axial ligand P450 mutant (C436S CYP2B4) all have very similar UV-Vis absorption and MCD spectra in the ferric state [27]. The results have led us to conclude that the latter two mutant heme proteins have an anionic oxygen atom donor ligated to the heme iron in a five-coordinate mode [27], as established for H93Y Mb [10], i.e., with an axial ligand being provided by tyrosinate for H93Y Mb, phenolate for H93G Mb and serinate for C436S CYP2B4.…”
Section: Discussionmentioning
confidence: 99%
“…The results have led us to conclude that the latter two mutant heme proteins have an anionic oxygen atom donor ligated to the heme iron in a five-coordinate mode [27], as established for H93Y Mb [10], i.e., with an axial ligand being provided by tyrosinate for H93Y Mb, phenolate for H93G Mb and serinate for C436S CYP2B4. To propose a basis (or bases) for the spectral differences (see Results, section 3.1) between this group of phenolate (or alkoxylate)-ligated (mutant) heme proteins and the aforementioned tyrosinate-ligated (native) heme enzymes (cAOS, MAP and BLC), we compare the active site structures of the latter three proteins with that of H93Y Mb in detail (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation